Optimizing Compost Quality: Decomposition Of Rice Straw Agro-Waste Through Various Biological Agent Supplementations - Priyadi, Priyadi; Mutaqin, Zainal; uana, Arum Sekar B; Maharani, Juwita Suri (Politeknik Negeri Bengkalis, 2024)
ntensive agricultural activities in rice cultivation impact increasing waste, especially straw. Unfortunately,straw contains cellulose and lignin, which are difficult to decompose. This study examines the effect of adding biologicalagents on compost quality from rice straw waste. The study used a Randomized Block Design (RBD) with four treatmentsand six replications, including T0: control (without biological agents), T1: POF catalyst, T2: Bacillus sp., T3: Trichodermasp. Observation variables for compost quality include analysis of temperature changes, pH value, water content, andchemical analysis, including the content of total macronutrients nitrogen, phosphorus, and potassium. Quantitative datawere analyzed statistically using ANOVA and the LSD test p <0.05. The findings indicated that incorporating biologicalagents in rice straw composting markedly enhanced the quality of the resulting compost. Utilizing biological agents,particularly the Trichoderma treatment, led to a notable enhancement in compost quality. The macronutrient content ofnitrogen (N) increased by 3.60%, phosphorus (P) by 0.49%, and potassium (K) by 1.67%. This increase could havesignificant implications for the composting process. Additionally, an increase in temperature, reaching 50-60°C,significantly impacts the composting process, collectively affecting microorganisms and facilitating the decomposition oforganic matter. Furthermore, the thermophilic phase in Trichoderma treatment accelerates decomposition, thus offering apotential solution for faster composting